2011
DOI: 10.1242/jcs.086694
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of adherens junction dynamics during apical–basal polarization

Abstract: SummaryAdherens junctions (AJs) in epithelial cells are constantly turning over to modulate adhesion properties under various physiological and developmental contexts, but how such AJ dynamics are regulated during the apical-basal polarization of primary epithelia remains unclear. Here, we used new and genetically validated GFP markers of Drosophila E-cadherin (DE-cadherin, hereafter referred to as DE-Cad) and bcatenin (Armadillo, Arm) to quantitatively assay the in vivo dynamics of biosynthetic turnover and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 54 publications
4
55
1
Order By: Relevance
“…3A). In addition, DECadASSA has significantly reduced biosynthetic turnover in polarizing cells and increased turnover in polarized cellsessentially a reversed differential regulation pattern of AJ dynamics compared with wild-type DE-Cad during cell polarization (Huang et al, 2011). Consistent with our whole-cell FRAP results, latrunculin treatment also showed that in DECadS4A-αCat and DE-CadASSA embryos the AJ-localized DECad, and presumably AJs, are more resistant to the loss of F-actin (Fig.…”
Section: Conserved Serine Residues Regulate the Biosynthetic Turnoversupporting
confidence: 86%
See 3 more Smart Citations
“…3A). In addition, DECadASSA has significantly reduced biosynthetic turnover in polarizing cells and increased turnover in polarized cellsessentially a reversed differential regulation pattern of AJ dynamics compared with wild-type DE-Cad during cell polarization (Huang et al, 2011). Consistent with our whole-cell FRAP results, latrunculin treatment also showed that in DECadS4A-αCat and DE-CadASSA embryos the AJ-localized DECad, and presumably AJs, are more resistant to the loss of F-actin (Fig.…”
Section: Conserved Serine Residues Regulate the Biosynthetic Turnoversupporting
confidence: 86%
“…Stage 9-11 embryos were selected for assaying polarizing epithelial cells and stage 15 embryos for assaying polarized cells. Whole-cell FRAP assays were performed in lateral epidermis (Huang et al, 2011). Although all DE-Cad* show reduced levels of β-Catenin in AJs in vivo, overall it appears that loss of phosphorylation potential of the SLSSLAS motif in DE-Cad does not significantly increase the biosynthetic instability of DE-Cad in AJs ( Fig.…”
Section: Conserved Serine Residues Regulate the Biosynthetic Turnovermentioning
confidence: 98%
See 2 more Smart Citations
“…The following fly strains were used: (Huang et al, 2011)], UAS-Lamp1:GFP (gift of H. Kramer, University of Texas Southwestern, Dallas, USA), SRF-GAL4 (gift of M. Metzstein, University of Utah, Salt Lake City, USA), btl-GAL4 and drm-GAL4 (Bloomington). EMS alleles of okg and cnj were generated previously (Ghabrial et al, 2011 RNAi, UAS-Tor.TED, Tor HMS01114 RNAi at 29°C.…”
Section: Fly Strainsmentioning
confidence: 99%